2023
DOI: 10.3390/diagnostics13020236
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Preclinical Assessment of the VEGF Targeting Potential of the Newly Synthesized [52Mn]Mn-DOTAGA-Bevacizumab Using Experimental Cervix Carcinoma Mouse Model

Abstract: Among humanized monoclonal antibodies, bevacizumab specifically binds to vascular endothelial growth factor A (VEGF-A). VEGF-A is an overexpressed biomarker in cervix carcinoma and is involved in the development and maintenance of tumor-associated neo-angiogenesis. The non-invasive positron emission tomography using radiolabeled target-specific antibodies (immuno-PET) provides the longitudinal and quantitative assessment of tumor target expression. Due to antibodies having a long-circulating time, radioactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…More recently, Csikos et al successfully synthesized a 52 Mn-DOTAGA-bevacizumab PET probe with high RCY and suitable stability properties for in vivo PET/MR imaging in a VEGF-A expressing KB-3-1 cervix carcinoma tumor-bearing mouse. 178 The quantitative PET images showed that the KB-3-1 tumors were recognizable from 4 h after injection, and the accumulation of radiopharmaceuticals increased with time and started to plateau 2-3 days (Figure 10B). Although it gradually declined over time, tumor-to-organ ratios remained high until the end of the study, and traditional Mn 2+ target organs such as the thyroid, liver, pancreas, and kidney had little tracer uptake.…”
Section: Manganese-52mentioning
confidence: 96%
See 4 more Smart Citations
“…More recently, Csikos et al successfully synthesized a 52 Mn-DOTAGA-bevacizumab PET probe with high RCY and suitable stability properties for in vivo PET/MR imaging in a VEGF-A expressing KB-3-1 cervix carcinoma tumor-bearing mouse. 178 The quantitative PET images showed that the KB-3-1 tumors were recognizable from 4 h after injection, and the accumulation of radiopharmaceuticals increased with time and started to plateau 2-3 days (Figure 10B). Although it gradually declined over time, tumor-to-organ ratios remained high until the end of the study, and traditional Mn 2+ target organs such as the thyroid, liver, pancreas, and kidney had little tracer uptake.…”
Section: Manganese-52mentioning
confidence: 96%
“…White arrows: subcutaneously growing KB-3-1 cervix tumors. 178 Reproduced with permission. 161 Copyright 2019, Royal Society of Chemistry.…”
Section: Zirconium-89mentioning
confidence: 99%
See 3 more Smart Citations